The Management of Posyandu Services in Providing Mealseas Rubella Vaccine at UPTD Puskesmas DTP Buntul Kemumu, Permata District, Bener Meriah Regency - Abu Bakar Sidik; Muhammad Bin Abubakar; Aiyub Aiyub (Master Program of Sociology, Universitas Malikussaleh,, 2020)
This study examines the management of posyandu services in administering mealseas rubella vaccine. The research objective was to understand how posyandu service management in administering mealseas rubella vaccine at UPTD Puskesmas DTP Buntul Kemumu, Permata District, Bener Meriah Regency and its obstacles. The theoretical perspective used is the theory of public service management. The research method used is a qualitative research method. The results showed that the functions and principles of management have not been implemented optimally, especially in relation to service strategy indicators, while other indicators have become obstacles in the implementation of health service delivery, namely the provision of the mealseas rubella vaccine at the UPTD Puskesmas DTP Buntul Kemumu, Permata District, Bener Meriah Regency. necessitating an increase in the active participation of puskesmas cadres in providing counseling, and a service system that must readjust to the applicable SOP. Meanwhile, the external obstacle is customers, namely recipients of the mealseas rubella vaccine, namely the public / parents who still do not want to give their children the vaccine because they are worried about the halal and haram content of the mealseas rubella vaccine.